Engineering CRISPR for emerging therapeutic applications - Xiaoqi Sun; Zhuang Liu (EngMedicine)
Clustered regularly interspaced short palindromic repeats (CRISPRs) were originally identified in bacterial and archaeal genomes as an adaptive immune response against invading viruses and phages. The discovery of the ability of CRISPR–Cas9 to cut targeted DNA sequences at predetermined sites has introduced a new era of precision and flexibility in genome editing. Building on this classic CRISPR–Cas system, the discovery of other diverse CRISPR systems and their further engineering have produced various powerful tools for gene editing and modulation at the genomic, chromatin, and RNA levels. This review summarizes the fundamental knowledge regarding CRISPR–Cas systems and explores the engineering strategies of these versatile systems for novel therapeutic applications. We discuss the evolution from classic CRISPR editing (CRISPR 1.0) to advanced methodologies such as base editing, prime editing, CRISPR-directed integrases, epigenetic editing, and RNA editing. This review focuses on the related principles, therapeutic applications, challenges, and future outlooks.